Deadline city: navigating the impacts of rapid urban redevelopment on belonging and identity in Singapore - Tan, Nurul Alexandria (Nanyang Technological University, 2024)
This study explores the complex impact of Singapore's rapid urban redevelopment on the cultural identity and sense of belonging among its residents. Through in-depth qualitative interviews, the research delves into the multifaceted significance of ordinary spaces that often go unnoticed, such as HDB void decks and shopping malls, which have traditionally served as vital hubs for social interaction and community bonding. The findings highlight the tension between progress and preservation, as participants grapple with the homogenization of the urban landscape, the erosion of cherished memories, and the desire for more inclusive, bottom-up approaches to decision-making. Drawing on the theoretical frameworks of high modernism and Orientalism, the analysis sheds light on how the state's pursuit of efficiency and global integration, influenced by its colonial legacy, has impacted the cultural vibrancy and community ties that have historically defined Singapore's built environment. The study offers insights into navigating the complex relationship between physical spaces, collective memories, and identity.